Multiple identities and crime: A study of Antillean women and girls in the Netherlands - Althoff, Martina (European Journal of Criminology, 2013)
The concept of intersectionality refers to the constructionist approach, which considers gender, class and race as categories of social inequality that cannot be added together but that intersect and construct each other. Social categories construct the social identities that affect what motivates people and how they operate. The question is how multiple identities come together in the context of crime? The paper reports the findings of a qualitative study that explored the concept of intersectionality when analysing crime. The study analysed the court files of Antillean women and girls living in the Netherlands and tried to find an explanation for their crime patterns in their struggle with their identity.
Keywords: LGBTQIA2+; antilles; approches et analyses; criminologie; discipline; europe; femmes* immigrantes; genre; identités; identités LGBTQIA2+; intersectionnalité; inégalités; pays-bas; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; violences; étude qualitative

Decolonizing feminism: Challenging connections between settler colonialism and heteropatriarchy - Arvin, Maile; Tuck, Eve; Morrill, Angie (Feminist Formations, 2013)
The article explores two intertwined ideas: that the United States is a settler colonial nation-state and that settler colonialism has been and continues to be a gendered process. The article engages Native feminist theories to excavate the deep connections between settler colonialism and heteropatriarchy, highlighting five central challenges that Native feminist theories pose to gender and women's studies. From problematizing settler colonialism and its intersections to questioning academic participation in Indigenous dispossession, responding to these challenges requires a significant departure from how gender and women's studies is regularly understood and taught. Too often, the consideration of Indigenous peoples remains rooted in understanding colonialism as an historical point in time away from which our society has progressed. Centering settler colonialism within gender and women's studies instead exposes the still-existing structure of settler colonialism and its powerful effects on Indigenous peoples and settlers. Taking as its audience practitioners of both "whitestream" and other feminisms and writing in conversation with a long history of Native feminist theorizing, the article offers critical suggestions for the meaningful engagement of Native feminisms. Overall, it aims to persuade readers that attending to the links between heteropatriarchy and settler colonialism is intellectually and politically imperative for all peoples living within settler colonial contexts.
Keywords: OFDIG; amériques; approches et analyses; colonialisme; féminisme autochtone; féminisme décolonial; intersectionnalité; militance; patriarcat; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; états-unis

Deconstructing privilege: Teaching and learning as allies in the classroom - Case, Kim (Routledge, 2013)
Although scholarly examinations of privilege have increased in recent decades, an emphasis on privilege studies pedagogy remains lacking within institutions. This edited collection explores best practices for effective teaching and learning about various forms of systemic group privilege such as that based on race, gender, sexuality, religion, and class. Formatted in three easy-to-follow sections, Deconstructing Privilege charts the history of privilege studies and provides intersectional approaches to the topic. Drawing on a wealth of research and real-life accounts, this book gives educators both the theoretical foundations they need to address issues of privilege in the classroom and practical ways to forge new paths for critical dialogues in educational settings. Combining interdisciplinary contributions from leading experts in the field-- such as Tim Wise and Abby Ferber-- with pedagogical strategies and tips for teaching about privilege, Deconstructing Privilege is an essential book for any educator who wants to address what privilege really means in the classroom.
Keywords: amériques; approches et analyses; discipline; intersectionnalité; inégalités; justice sociale; outils; ouvrages de références; privilèges; régions géographiques; sciences de l'éducation; systèmes d'oppressions; états-unis

Politiques d’immigration : femmes et violence conjugale dans le contexte québécois - Castro Zavala, Sastal (Alterstice, 2013)
Si les femmes immigrent presque dans la même proportion que les hommes, elles sont plus vulnérables qu’eux à la violence et à l’exploitation. Les résultats de recherches réalisées auprès de femmes immigrantes et d’intervenantes sociales montrent que l’immigration peut entre autres déclencher ou augmenter la vulnérabilité des femmes à la violence conjugale. Cet article met l’accent sur la manière dont les politiques d’immigration interagissent avec d’autres formes d’oppression dans la vie des femmes immigrantes et donc participent à cette vulnérabilisation. À partir d’une recension des écrits sur la violence conjugale en contexte d’immigration et de documents sur l’impact des politiques d’immigration sur les droits des femmes, et en utilisant la théorie féministe intersectionnelle comme cadre d’analyse, nous traitons de la problématique de la violence conjugale en contexte d’immigration. Cela nous permet d’expliquer comment des facteurs comme le statut d’immigration, le genre, la classe sociale ou la race placent les femmes, notamment immigrantes, dans une position sociale qui les vulnérabilise davantage à la violence conjugale.
Keywords: amériques; approches et analyses; cours; discipline; femmes immigrantes; intersectionnalité; politiques migratoires; précarité; québec; ressource en ligne; régions géographiques; sciences humaines; soc1061; thématiques; travail social; violences; violences conjugales; violences économiques

Les filles en série: des Barbies aux Pussy Riot - Delvaux, Martine (Les éditions du remue-ménage, 2013)
Des corps féminins en rangées, qui se meuvent en synchronie. Ils ne se distinguent que par le détail d’un vêtement, d’une courbe, d’une teinte de cheveux. Les filles en série créent l’illusion de la perfection. Ce sont des filles-machines, filles-marchandises, filles-ornements. Toutes reproduites mécaniquement par l’usine ordinaire de la misogynie. Les filles sont des filles parce qu’elles sont en série. Mais la figure des filles en série est double: à la fois serial girls et serial killers de l’identité qu’on cherche à leur imposer. Entre aliénation et contestation, les filles en série résistent à leur chosification, cassent le party, libèrent la poupée et se mettent à courir. Cet essai percutant, paru pour la première fois en 2013, se déploie comme une chaîne qui se fait et se défait, depuis les Cariatides jusqu’aux Pussy Riot. Dans cette édition revue et augmentée, Martine Delvaux s’attaque à la blancheur des filles en série et analyse de nouvelles formes de résistance investies par les ballerines, les survivantes d’agressions et Beyoncé.
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; discours dominant; fem1000; fem3500; fem7000; histoire de l'art; histoire et politique; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit3220; militance; premier cycle; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Le travail social: théories, méthodologies et pratiques - Dorvil, Henri; Harper, Elizabeth; Bibliothèque numérique canadienne (Firme) (Collection Problèmes sociaux & interventions sociales, 2013)
"Ce livre vise à introduire de nouvelles façons de concevoir, de théoriser et d'intervenir sur le social en ce xxie siècle. Il y est non seulement question des fondements du travail social, mais aussi des politiques sociales, des méthodes d'intervention et des enjeux contemporains de la profession. En revisitant d'une manière créative les postulats de base du travail social, les auteurs proposent des lectures inédites des problèmes sociaux, un regard plus nuancé sur les populations marginalisées, un renouvellement des politiques sociales comme levier de citoyenneté ainsi que des pistes d'intervention plus respectueuses des individus, des groupes, des familles et des communautés."-- Site de l'éditeur.
Keywords: approche interculturelle; approches et analyses; cours; discipline; histoire et politique; intersectionnalité; outils; ouvrages de références; premier cycle; sciences humaines; sciences sociales; sex2283; thématiques; travail; travail social

Feminist, queer, crip - Kafer, Alison (Indiana University Press, 2013)
Select all Front Matter (pp. i-vi) Front Matter (pp. i-vi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.1 Table of Contents (pp. vii-viii) Table of Contents (pp. vii-viii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.2 Acknowledgments (pp. ix-xii) Acknowledgments (pp. ix-xii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.3 Textual Description of the Cover Art (pp. xiii-xvi) Textual Description of the Cover Art (pp. xiii-xvi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.4 Introduction: Imagined Futures (pp. 1-24) Introduction: Imagined Futures (pp. 1-24) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.5 I have never consulted a seer or psychic; I have never asked a fortune-teller for her crystal ball. No one has searched my tea leaves for answers or my stars for omens, and my palms remain unread. But people have been telling my future for years. Of fortune cookies and tarot cards they have no need: my wheelchair, burn scars, and gnarled hands apparently tell them all they need to know. My future is written on my body. In 1995, six months after the fire, my doctor suggested that my thoughts of graduate school were premature, if not misguided. He... 1 Time for Disability Studies and a Future for Crips (pp. 25-46) 1 Time for Disability Studies and a Future for Crips (pp. 25-46) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.6 What would it mean to explore disability in time or to articulate “crip time”? Temporal categories are already commonly used in formulations of disability; one aspect of cripping time might simply be to map the extent to which we conceptualize disability in temporal terms. The medical field in particular has a long tradition of describing disability in reference to time. “Chronic” fatigue, “intermittent” symptoms, and “constant” pain are each ways of defining illness and disability in and through time; they describe disability in terms of duration. “Frequency,” “incidence,” “occurrence,” “relapse,” “remission”: these, too, are the time frames of symptoms, illness,... 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.7 In thinking about crip futurity, I find myself haunted by Ashley X. Born in 1997, the girl known as Ashley X was diagnosed with “static encephalopathy” a few months after her birth. “In the ensuing years,” doctors note, “her development never progressed beyond that of an infant,” and her doctors held no hope that her cognitive or neurological baseline would improve.¹ “At the age of 6 years, she [could] not sit up, ambulate, or use language.”² Concerned about their daughter’s long-term future, Ashley’s parents met with doctors in 2004 to discuss the potential effects of puberty and physical growth on... 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.8 The pervasiveness of prenatal testing, and especially its acceptance as part of the standard of care for pregnant women, casts women as responsible for their future children’s able-bodiedness/able-mindedness; prospective parents are urged to take advantage of these services so as to avoid burdening their future children with any disabilities.¹ This notion of “burdening” children finds an echo in the debate over same-sex marriage, with LGBT couples cast as selfish parents, placing their own desires over the physical and mental health of their children (and, by extension, of all children). Moreover, according to Timothy Dailey of the Family Research Council, homosexual... 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.9 “Super man,” the billboard exclaims, the unfamiliar gap between the two words emphasizing both the noun and its adjective. Below this phrase is the word “STRENGTH,” followed by the imperative “Pass It On.” At the bottom, in small print, runs the name and web address of the organization behind this public relations campaign: Values.com/Foundation for a Better Life. The “super man” referenced in the caption is, of course, the late Christopher Reeve, the white actor who starred in a series ofSupermanfilms in the 1980s before becoming a quadriplegic in a riding accident in 1995. A black-and-white photograph of... 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.10 Controversy came quickly to the cyborg. In 1983,Socialist Reviewinvited several feminist theorists, among them Donna Haraway, “to write about the future of socialist feminism in the context of the early Reagan era.”¹ Haraway responded with “A Manifesto for Cyborgs,” framing the cyborg as a figure of feminist critique.² Her cyborg was a radical border-crosser, blurring the boundaries between human and animal, machine and organism, physical and non-physical.³ Such a cyborg, she argued, could “guide us to a more livable place,” an “elsewhere,” in which “people are not afraid of their joint kinship with animals and machines, not afraid... 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.11 Although concern with the environment has long been an animating force in disability studies and activism, “environment” in this context typically refers to the built environment of buildings, sidewalks, and transportation technologies. Indeed, the social model of disability is premised on concern for the built environment, stressing that people are disabled not by their bodies but by their inaccessible environments. (The wheelchair user confronting a flight of steps is probably the most common illustration of this argument.) Yet the very pervasiveness of the social model has prevented disability studies from engaging with the wider environment of wilderness, parks, and nonhuman... 7 Accessible Futures, Future Coalitions (pp. 149-170) 7 Accessible Futures, Future Coalitions (pp. 149-170) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.12 When describing disability studies to my students, I often draw on Douglas Baynton’s insight that “disability is everywhere in history once you begin looking for it.”¹ For Baynton, “looking for it” entails not only recovering the stories of disabled people or tracing histories of disability discrimination but also exploring how notions of disability and able-mindedness/able-bodiedness have functioned in different contexts. Baynton issues his provocation to historians, but disability studies scholars in other fields have extended its reach, pushing their own colleagues to recognize disability as a category of analysis. Deeply influenced by and indebted to this work, I use this... Appendices (pp. 171-178) Appendices (pp. 171-178) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.13 Notes (pp. 179-224) Notes (pp. 179-224) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.14 Bibliography (pp. 225-252) Bibliography (pp. 225-252) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.15 Index (pp. 253-258) Index (pp. 253-258) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.16 Back Matter (pp. 259-259) Back Matter (pp. 259-259) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.17 Indiana University Press logo Front Matter Download XML Table of Contents Download XML Acknowledgments Download XML Textual Description of the Cover Art Download XML Introduction:: Imagined Futures Download XML Time for Disability Studies and a Future for Crips Download XML At the Same Time, Out of Time:: Ashley X Download XML Debating Feminist Futures:: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians Download XML A Future for Whom?: Passing on Billboard Liberation Download XML The Cyborg and the Crip:: Critical Encounters Download XML Bodies of Nature:: The Environmental Politics of Disability Download XML Accessible Futures, Future Coalitions Download XML Appendices Download XML Notes Download XML Bibliography Download XML Index Download XML Back Matter Download XML ABOUT US About JSTOR Mission and History JSTOR Labs JSTOR Daily News Webinars Careers EXPLORE CONTENT What's in JSTOR Advanced Search By Subject By Title Collections Publisher Images RESEARCH TOOLS Data for Research The JSTOR Understanding Series Constellate HELP CENTER Get Support Get Access LibGuides Research Basics Contact Us For Librarians For Publishers Teaching Resources JSTOR is part of ITHAKA, a not-for-profit organization helping the academic community use digital technologies to preserve the scholarly record and to advance research and teaching in sustainable ways.©2000‍–2024 ITHAKA. All Rights Reserved. JSTOR®, the JSTOR logo, JPASS®, Artstor®, Reveal Digital™ and ITHAKA® are registered trademarks of ITHAKA. Terms & Conditions of Use Privacy Policy Accessibility Cookie Policy Cookie Settings Description In Feminist, Queer, Crip Alison Kafer imagines a different future for disability and disabled bodies. Challenging the ways in which ideas about the future and time have been deployed in the service of compulsory able-bodiedness and able-mindedness, Kafer rejects the idea of disability as a pre-determined limit. She juxtaposes theories, movements, and identities such as environmental justice, reproductive justice, cyborg theory, transgender politics, and disability that are typically discussed in isolation and envisions new possibilities for crip futures and feminist/queer/crip alliances. This bold book goes against the grain of normalization and promotes a political framework for a more just world.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; care; corps; cours; crip; discipline; future; identités LGBTQIA2+; intersectionnalité; justice sociale; philosophie; premier cycle; périodes historiques; queer; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1920; thématiques; études critiques du handicap

Femmes et handicap - Masson, Dominique (Recherches féministes, 2013)
Les femmes handicapées, leurs réalités et leurs combats sont encore largement absents du courant de pensée majoritaire (mainstream) en études féministes qui, malgré un virage récent vers les analyses intersectionnelles, demeurent peu au fait des modalités d'analyse du handicap et des oppressions fondées sur les (in)capacités. Cet article veut permettre à un lectorat francophone de se familiariser avec les principales bases conceptuelles utilisées pour théoriser le handicap et les (in)capacités développées dans le domaine des études critiques du handicap, et en particulier par les auteures féministes travaillant dans ce champ. Il vise également à contribuer aux connaissances féministes des enjeux de transformation sociopolitique qui sont centraux pour les femmes handicapées, tels que ceux-ci sont révélés par les luttes de l'organisation féministe Action des femmes handicapées (Montréal). En conclusion, l'auteure explique la raison pour laquelle le handicap doit être considéré comme un enjeu féministe
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; canada; capacitisme; care; corps; cours; discipline; histoire et politique; intersectionnalité; justice sociale; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études féministes

Towards an Australian Indigenous Women's Standpoint Theory - Moreton-Robinson, Aileen (Australian feminist studies, 2013)
In this article I outline an Australian Indigenous women's standpoint theory. I argue that an Indigenous women's standpoint generates problematics informed by our knowledges and experiences. Acknowledging that Indigenous women's individual experiences will differ due to intersecting oppressions produced under social, political, historical and material conditions that we share consciously or unconsciously. These conditions and the sets of complex relations that discursively constitute us in the everyday are also complicated by our respective cultural differences and the simultaneity of our compliance and resistance as Indigenous sovereign female subjects.
Keywords: approches et analyses; australie; cours; droits des femmes*; féminisme autochtone; histoire et politique; intersectionnalité; point de vue situé; pol4212; premier cycle; ressource en ligne; régions géographiques; thématiques

Vieillissement réussi : perception des femmes aînées immigrantes de l’Afrique noire à Montréal - Noubicier, Agnès Florette; Charpentier, Michèle (Santé mentale au Québec, 2013)
Le présent article s’intéresse aux femmes aînées des communautés ethnoculturelles de l’Afrique noire. Il a pour but de présenter le sens qu’elles donnent au « vieillissement réussi » dans leur pays d’accueil, et de mettre en évidence les facteurs qu’elles considèrent comme essentiels pour expérimenter « un maximum de satisfaction et de bonheur » au cours de cette étape de leur vie. Il s’appuie sur une étude qualitative exploratoire menée auprès de sept femmes âgées de 65 à 77 ans qui ont immigré au Québec alors qu’elles avaient plus de 50 ans. L’étude met en relief des femmes aux identités multiples et aux vieillissements différentiels, pour qui le « vieillissement réussi » est tributaire de leur implication dans la famille et dans la société, de la foi et de l’autonomie financière. L’analyse des résultats sous un angle intersectionnel permet aussi de noter que les femmes aînées immigrantes de l’Afrique noire connaissent des difficultés en raison de l’entrecroisement des effets dus à leur âge, leur appartenance ethnique et leur genre, avec d’autres aspects liés à leur identité tels que la culture, la langue, le sexe, le parcours migratoire. Une multitude d’obstacles jonchent alors leur processus de vieillissement et influent sur leur conception du « vieillissement réussi
Keywords: 2000 à aujourd'hui; accomplissement; afrique; afrique noire; amériques; approches et analyses; cours; discipline; femmes aînées; femmes immigrantes; intersectionnalité; périodes historiques; québec; récits de vie; régions géographiques; santé; santé mentale; sciences humaines; soc1061; sociologie; thématiques; travail social; vieillissement

Où en sommes-nous avec l'art féministe? : analyse de la programmation de la Centrale Galerie Powerhouse (1973-1978 et 2007-2010) - Rondeau, Kim (Université du Québec à Montréal, 2013)
Au cours des 10 dernières années, de nombreux évènements en arts visuels se sont penchés sur la question du féminisme, malgré l'annonce de la mort de ce courant politique par plusieurs discours populaires. Effectivement, l'avènement, à la fin de la décennie 1980, des champs d'études queer et postcoloniales reconceptualise et complexifie le sujet du féminisme, la femme. Les fondements de l'identité femme, la fixité de cette catégorie, se voient maintenant interroger. De ce fait, les prémisses misent de l'avant par les féministes des années 1970, moment fort du mouvement de libération des femmes, reçoivent un lot important de critique. Dans un tel contexte, nous souhaitons questionner l'art féministe actuel et comment il se manifeste. Plus spécifiquement, nous voulons analyser de quelle façon il diffère des pratiques féministes inaugurés dans la décennie 1970. C'est sur cette problématique que s'attarde ce mémoire prenant pour corpus d'études les expositions présentées, de 1973 à 1978 et de 2007 à 2010, au centre d'artistes féministes montréalais La Centrale Galerie Powerhouse. Ce lieu de diffusion, fondé par des femmes désirant avoir un endroit pour exposer leur art à un moment où elles étaient exclues des institutions, est un témoin privilégié des relations qu'entretiennent le discours artistique et les théories féministes. La Centrale Powerhouse a d'ailleurs modifié son mandat en 2008 dans le but de demeurer pertinent face aux changements ayant lieu au sein du courant féministe. À travers notre étude comparative de la programmation du centre d'artistes, nous voulons démontrer des démarches politisées, enrichies par de nouvelles préoccupations queer et postcoloniales, demeurent possible ainsi qu'une lecture féministe des œuvres. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Art féministe, art contemporain, La Centrale Galerie Powerhouse
Keywords: IREF; amériques; analyse comparée; approches et analyses; art féministe; arts; discipline; histoire de l'art; intersectionnalité; mémoires/thèses; queer; québec; ressource en ligne; régions géographiques

Race, gender, class, sexuality (RGCS) and hypertension - Veenstra, Gerry (Social Science & Medicine, 2013)
Informed by intersectionality theory, a tradition that theorizes intersecting power relations of racism, patriarchy, classism and heterosexism, this paper investigates the degree to which race, gender, class and sexuality manifest distinct and interconnected associations with self-reported hypertension in nationally-representative survey data from Canada. Binary logistic regression is used to model the main effects of, and interactions between, race, gender, education, household income and sexual orientation on hypertension, controlling for age, using data from the 2003 Canadian Community Health Survey (n = 90,310). From a main effects (‘additive’) perspective, Black respondents, respondents with less than high school and poorer respondents were significantly more likely than White respondents, university-educated Canadians and wealthier Canadians, respectively, to report hypertension. However, the interactive models indicate that the additive models were poor predictors of hypertension for wealthy Black men, wealthy South Asian women, women with less than a high school diploma and wealthy bisexual respondents, who were more likely than expected to report hypertension, and for poor Black men, poor South Asian women, poor South Asian men and women with a university degree, who were less likely than expected to report hypertension. It appears that, with regard to blood pressure at least, Canadians experience the health effects of education differently by their genders and the health effects of income differently by their identities defined at the intersection of race and gender. This study provides empirical support for the intersectional approach to cardiovascular health inequalities by demonstrating that race, gender, class and sexuality cannot be disentangled from one another as predictors of hypertension.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; discipline; hétérosexisme; intersectionnalité; médecine; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé cardiovasculaire; sciences; sexisme; systèmes d'oppressions; thématiques

Genre, migrations et globalisation de la reproduction sociale - Verschuur, Christine; (Dir), Christine Catarino; Par, Dirigé. (L'Harmattan, 2013)
Les études féministes ont souligné l’importance d’étudier le travail auparavant invisible des femmes, productif et reproductif, et la nouvelle division du travail productif et reproductif dans la mondialisation du capitalisme. L’analyse du capitalisme mondialisé dans une perspective décoloniale permet de comprendre qu’il n’est pas seulement un système économique ni seulement un système culturel mais un réseau global de pouvoir intégré par des processus économiques, politiques et culturels qui constituent un ensemble. Partout on observe un système, social, économique, culturel, moral d’organisation de la reproduction sociale, y compris le care, entendu comme échange économico-affectif, qui implique des biens et des services liés à l’économie capitaliste. Dans le nouvel ordre économique global, que l’on pourrait toujours qualifier de colonial, caractérisé par la nouvelle division internationale du travail, l’articulation entre rapports sociaux dans l’économie domestique et capitaliste prend de nouvelles formes. Mais le système repose toujours sur l’organisation de l’ensemble des activités et des rapports indispensables à la reproduction sociale, par-delà les frontières, dans des réseaux et foyers transnationaux, en s’appuyant sur des discours de genre et de race, voire de classe. Dans ce système, les femmes migrantes sont particulièrement présentes. Elles constituent un maillon essentiel du système de protection sociale aux Nords, y contribuent à la production de richesses, tout en assurant l’organisation de la reproduction sociale aux Suds, dans les foyers qu’elles ont gardés dans leurs pays d’origine.
Keywords: approches et analyses; capitalisme; care; cours; discipline; féminisme décolonial; globalisation; intersectionnalité; justice sociale; militance; pol4022; premier cycle; ressource en ligne; science politique; science politique et droit; sciences humaines; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; travail; travail du sexe